Analysis of mid-trimester maternal serum β-hCG and AFP as markers of preterm and term adverse pregnancy outcomes form a tertiary care hospital, Morang, Nepal - Mallick, Ram L.; Gaire, Chandra Prakash; Dahal, Prerana; Kafle, Neeta (Journal of Biomedical Sciences, 2023)
Background: Mid-trimester maternal serum markers have been used for prenatal aneuploidy screening for a long time. The aim of the study was to assess the mid-term serum levels of β-human chorionic gonadotropin and alpha-fetoproteins for placenta-mediated adverse pregnancy outcomes (PMAPOs) in preterm and term pregnancies. Material and methods: A prospective cohort study involving nulliparous women with singletons without aneuploidy or fatal fetal abnormalities was carried out a tertiary care hospital, Morang, Nepal. AFP and β-hCG levels were estimated between 13 and 17 weeks of gestation in the mother's serum. All values were in multiples of the median (MoM) and compared between women with PMAPOs. Results: The serum levels of AFP and β-hCG were obtained in 176 out of 300 nulliparous women. The MoM of serum β-hCG (1.3 vs 1.1) and AFP (1.4 vs 1.1) were higher in PMAPOs-affected women than in controls. Conclusion:Preterm PMAPOs, but not term PMAPOs, are more likely in the present study when maternal serum AFP or β -hCG levels are more significant than 2.0 MoM. If fetal growth is within the normal range at 37 weeks of gestation, it is advisable that women with increased serum β-hCG or AFP receive regular prenatal care.